An aggressive fibromatosis in the palm of a female child: A rare case - Napit, Arun Ranjan; Panchal, Shraddha; Panchal, Dhaval (Indian Journal of Case Reports, 2021)
Aggressive fibromatosis is the locally aggressive benign tumor of mesenchymal origin. It can be found in any part of the body. However, abdomen is the most common site of this lesion. It has a predilection to females between 15 and 60 years. We report the case of a 16-month-old female child with an aggressive fibromatosis in her right palm. The location and age of presentation make this a rare case. She was diagnosed by histopathological examination and the mass was excised. The patient was advised for follow-up examination due to the high degree of recurrence of this tumor.